In vitro α-amylase and α-glucosidase inhibitory activity of Ononis angustissima extracts - Hind Laoufi, Nabila Benariba, Sara Adjdir, Rabah Djaziri (Journal of Applied Pharmaceutical Science, 2017)
The purpose of present study was to investigate the effects of extracts of O. angustissima a traditional medicinal plant, on α-amylase and α-glucosidase activities in vitro. The air-dried aerial parts of O. angustissima flowers, leaves and stems were extracted with distilled water (AE) and aqueous methanol (MeOH-H2O); ethyl acetate (EtAOc) and n-butanol extracts (n-BuOH) were obtained from MeOH-H2O crude extracts per liquid/liquid extraction. The results of the both enzyme inhibition activity was found in a dose-dependent manner, The strongest activity in case of α- glucosidase was shown by MeOH-H2O and n-BuOH extracts of O. angustissima with IC50 value 0.94 and 0.99 mg/mL, respectively, whereas AE and EtOAc extract showed 1.10 and 1.17 mg/mL as IC50 value respectively compared with the standard acarbose having IC50 value 0.046 mg/mL. Whereas the higher activity in case of α-amylase inhibition, was found in MeOH-H2O extract (IC50 = 2.01 mg/mL) followed by AE (2.52 mg/mL) and n-BuOH extract (2.88 mg/mL) respectively, compared with acarbose having IC50 value of 0.044 mg/mL. All extract from this plant possess moderate α-amylase inhibition with potent α-glucosidase inhibitory activity which may offer better therapeutic strategy to minimized postprandial hyperglycemia and its complications.
Keywords: &alpha; - glucosidase inhibition, &alpha; -amylase inhibition, Fabaceae, Ononis angustissima, polyphenols, flavonoids.